Relationship between body weight and body condition score with energy content in the carcass of Pelibuey ewes - Díaz-López, Gustavo; Salazar-Cuytun, Rosario; García Herrera, Ricardo; Piñeiro-Vázquez, Angel; Casanova-Lugo, Fernando; Chay-Canul, Alfonso J (Austral Journal of Veterinary Sciences, 2017)
The determination of energy content in the carcass and body of domestic animals by direct method involves very intensive work and it is costly. The aim of this study was to evaluate the relationship between body weight (BW) and body condition score (BCS) with the energy content of muscular and adipose tissues of adult Pelibuey ewes. Twenty two adult non-pregnant, nonlactating ewes of 35.63 ± 5.03 kg BW and 2.47±0.55 BCS were used. The correlation coefficients (r) of BCS between muscle energy (ME), fat energy (FE) and total energy (TE) were all significant (P<0.01) with values of 0.64, 0.66 and 0.69, respectively, while for BW between ME, FE and TE they were all significant (P<0.001) with values of 0.90, 0.76 and 0.89, respectively. The regression equations had high determination coefficients (r2) ranging from 0.87 to 0.94 when BCS was used as predictor, while using the BW the r2 ranged from 0.59 to 0.83. The inclusion of both BW and BCS in multiple regressions improved the prediction from 2 to 7%; nonetheless, the inclusion of BCS only was significant in the equation for TE. The use of BCS and BW in Pelibuey ewes provides a good estimate of the ME, TE and FE of the carcass.